(untitled) (World Economics and Finance Bulletin, 2024)
This article discusses the integration of taxation and local governance in tax capacity building. The research considered the theoretical foundations of the concept of harmony between taxation and local government bodies, determined the role of taxes in the formation of budgets of local government bodies, as well as the advanced international practice of harmonizing these two important elements of the social system. experiments were studied. The methodological part of the work includes the analysis of existing methods and models of coordination between tax and local authorities, as well as the identification of problems and obstacles in their mutual relations. Specific measures to optimize cooperation between tax authorities and local government authorities aimed at increasing the efficiency and transparency of this process were proposed